Cross-species complementation of bacterial- and eukaryotic-type cardiolipin synthases - Petra Gottier; Mauro Serricchio; Rita Vitale; Angela Corcelli; Peter Bütikofer (Microbial Cell, 2017)
The glycerophospholipid cardiolipin is a unique constituent of bacterial and mitochondrial membranes. It is involved in forming and stabilizing high molecular mass membrane protein complexes and in maintaining membrane architecture. Absence of cardiolipin leads to reduced efficiency of the electron transport chain, decreased membrane potential, and, ultimately, impaired respiratory metabolism. For the protozoan parasite Trypanosoma brucei cardiolipin synthesis is essential for survival, indicating that the enzymes involved in cardiolipin production represent potential drug targets. T. brucei cardiolipin synthase (TbCLS) is unique as it belongs to the family of phospholipases D (PLD), harboring a prokaryotic-type cardiolipin synthase (CLS) active site domain. In contrast, most other eukaryotic CLS, including the yeast ortholog ScCrd1, are members of the CDP-alcohol phosphatidyl transferase family. To study if these mechanistically distinct CLS enzymes are able to catalyze cardiolipin production in a cell that normally expresses a different type of CLS, we expressed TbCLS and ScCrd1 in CLS-deficient yeast and trypanosome strains, respectively. Our results show that TbCLS complemented cardiolipin production in CRD1 knockout yeast and partly restored wild-type colony forming capability under stress conditions. Remarkably, CL remodeling appeared to be impaired in the transgenic construct, suggesting that CL production and remodeling are tightly coupled processes that may require a clustering of the involved proteins into specific CL-synthesizing domains. In contrast, no complementation was observed by heterologous expression of ScCrd1 in conditional TbCLS knockout trypanosomes, despite proper mitochondrial targeting of the protein.